2014
DOI: 10.1177/0036933014556051
|View full text |Cite
|
Sign up to set email alerts
|

Hamman and Boerhaave syndromes – diagnostic dilemmas in a patient presenting with hyperemesis gravidarum: a case report

Abstract: Subcutaneous emphysema is an alarming finding in any pregnancy and should be treated in a timely and cautious manner. This case report adds weight to the previous literature advocating a conservative versus surgical approach to the management of a woman with Hamman syndrome secondary to hyperemesis gravidarum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…While some patients with this complication may tolerate conservative management, others may require surgical intervention. This complication may be suspected in patients presenting with subcutaneous emphysema on physical exam or imaging [25]. …”
Section: Maternal Complicationsmentioning
confidence: 99%
“…While some patients with this complication may tolerate conservative management, others may require surgical intervention. This complication may be suspected in patients presenting with subcutaneous emphysema on physical exam or imaging [25]. …”
Section: Maternal Complicationsmentioning
confidence: 99%
“…In addition, women with HG also can have excess salivation (Godsey et al, 1991), vitamin B1 and mineral deficiencies (Koch et al, 2003), gastroesophageal reflux symptoms and abnormal liver function tests (Lee et al, 2011). HG is associated with morbidity such as acute kidney injury (Machado et al, 2012), liver dysfunction (Shekhar et al, 2015), pneumomediastinum (Gorbach et al, 1997; Liang et al, 2002), ruptured esophagus (Buchanan et al, 2014), and Wernicke’s encephalopathy (Berdai et al, 2016; Giugale et al, 2015). In addition, a recent case-control study found that psychological distress was a direct consequence of HG (Aksoy et al, 2015), which is in accordance with previous reports of increased risk of cognitive, behavioral, and emotional disorders in this population (Poursharif et al, 2008; Zur, 2013).…”
Section: Hyperemesis Gravidarummentioning
confidence: 99%
“…As such the initial diagnosis is only made in one third of cases [ 6 ]. Boerhaave’s syndrome most commonly presents in older males secondary to excessive alcohol consumption, neurological disease, severe esophageal burns, and scleroderma [ 7 ]. Vomiting is a known predisposing factor in the published case reports of spontaneous esophageal perforations in first trimester, late pregnancy, and postpartum, with only one other case report documenting a spontaneous esophageal rupture in pregnancy in the absence of any vomiting antenatally or intrapartum [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Valsalva maneuver during forced expiration is repeated constantly during pushing causing alveolar barotrauma. Air then travels from the damaged alveoli through sheaths to the mediastinum and into the subcutaneous tissue [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation